Characterization of encapsulation process of avobenzone in solid lipid microparticle using a factorial design and its effect on photostability (2014)
ABSTRACT: Avobenzone (AVO)liposphereswere obtained using as encapsulating material carnauba wax and applying the method of hot emulsification. A factorial design 23 was performed to optimize and recognize the influence of the initial amount of AVO, the stearyl alcohol (SA) and polysorbate (PS-20)concentrationsin the AVO loading, mean and D90 particle size. The results showed a variation of AVO loading between 1.8 and 20%, which was mainly affected by initial amount of AVO. The mean particle size D [4.3] ranged from 11.11 to 37.15 μm, this was affected by the levels of SA and PS-20, while D90 was influenced by three variables under study. Lipospheres highly loaded and under a narrow particle distribution was obtained when initial amount of AVO, SA and PS-20 were set in the maximum level. The study showed that the encapsulation process enhanced the photostability going from 31.5% for free AVO to 16.2% for the encapsulated AVO.